Combining loss of function of FOLYLPOLYGLUTAMATE SYNTHETASE1 and CAFFEOYL-COA 3-O-METHYLTRANSFERASE1 for lignin reduction and improved saccharification efficiency in Arabidopsis thaliana - Xie, Hongli (Biotechnol Biofuels, 2019)
BACKGROUND: Downregulation of genes involved in lignin biosynthesis and related biochemical pathways has been used as a strategy to improve biofuel production. Plant C1 metabolism provides the methyl units used for the methylation reactions carried out by two methyltransferases in the lignin biosynthetic pathway: caffeic acid 3-O-methyltransferase (COMT) and caffeoyl-CoA 3-O-methyltransferase (CCoAOMT). Mutations in these genes resulted in lower lignin levels and altered lignin compositions. Reduced lignin levels can also be achieved by mutations in the C1 pathway gene, folylpolyglutamate synthetase1 (FPGS1), in both monocotyledons and dicotyledons, indicating a link between the C1 and lignin biosynthetic pathways. To test if lignin content can be further reduced by combining genetic mutations in C1 metabolism and the lignin biosynthetic pathway, fpgs1ccoaomt1 double mutants were generated and functionally characterized. RESULTS: Double fpgs1ccoaomt1 mutants had lower thioacidolysis lignin monomer yield and acetyl bromide lignin content than the ccoaomt1 or fpgs1 mutants and the plants themselves displayed no obvious long-term negative growth phenotypes. Moreover, extracts from the double mutants had dramatically improved enzymatic polysaccharide hydrolysis efficiencies than the single mutants: 15.1% and 20.7% higher than ccoaomt1 and fpgs1, respectively. The reduced lignin and improved sugar release of fpgs1ccoaomt1 was coupled with changes in cell-wall composition, metabolite profiles, and changes in expression of genes involved in cell-wall and lignin biosynthesis. CONCLUSION: Our observations demonstrate that additional reduction in lignin content and improved sugar release can be achieved by simultaneous downregulation of a gene in the C1 (FPGS1) and lignin biosynthetic (CCOAOMT) pathways. These improvements in sugar accessibility were achieved without introducing unwanted long-term plant growth and developmental defects. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13068-019-1446-3) contains supplementary material, which is available to authorized users.